Integration of item response theory in the development of PhET-based graphing lines worksheets for optimizing student algebra competence - Giyanti; Lestari, Indri; Oktaviyanthi, Rina (Jurnal Elemen, 2025)
This study develops and evaluates a graphing line worksheet based on PhET Interactive Simulation integrated with Item Response Theory (IRT) methods to enhance student algebra competence. Involving 120 students, the worksheet comprises 12 items measuring four key indicators: understanding the geometric significance of line slopes, constructing line equations, graphing from line equations, and predicting the effects of variable changes. The 2-Parameter Logistic (2PL) model of IRT was employed to analyze item difficulty and student ability in logit form. The results indicate that the worksheet is effective in improving student algebra competence, with Items 1 and 11 demonstrating a good balance between difficulty and discrimination. Item 2 requires further review because of its high difficulty, whereas Item 12 is considered too easy. Heatmap analysis and Item Characteristic Curves (ICC) revealed variations in student response patterns, confirming the test's ability to evaluate diverse levels of student ability. The integration of interactive simulation and IRT has proven to be an effective strategy in instructional design, supporting adaptive and personalized learning.